Kajian Teknis Geometri Jalan Angkut dan Pengaruhnya Terhadap Produksi Alat Angkut pada Penambangan Batu Andesit di PT. Ansar Terang Crushindo 1Kecamatan Pangkalan Koto Baru, Sumatera Barat. - Mutia Zara; Heri Prabowo (Journals Mining Engineering : Bina Tambang, 2020)
Abstract: PT. Ansar Terang Crushindo is andesite mining company located in Kecamatan Pangkalan Koto Baru, Kabupaten  Lima Puluh Kota. The monthly target production PT. Ansar Terang Crushsindo is 20,000 tons / month, while the actual production in November was 15,608.8 tons / month. One of the factors that affect the non-achievement of production targets is the condition of the haul road. Based on observations in the field, there grades above 8%, the width of the haul roads has not met the standards so that when one passes, one of the conveyances must stop and there is no cross slope and safety berm. Based on the measurement of haul road geometry, it is found that the actual road width ranges from 3.68 to 6.2 meters, while theoretically the straight road width is 9 meters. The actual curved road width ranges from 3.54 to 6.4 meters, while the theoretical curved road width is 12.2 meters. actual road grade is from 3.54% to 11.68%. Meanwhile, ideal road grade is 8%. The cross slope value for a road width of 9 meters is 0.04 and a height difference of 17.1 cm. the superelevation value for the bend width of 12.2 meters is 0.04 and the height difference is 48 cm. After being evaluated, there are 5 straight road segments are necessary to add width and 4 segment of road bends, and lower grade in 4 segments. Mitsubishi Fuso 250 PS production in actual conditions was 15,367.62 tons / month. The estimated production of the Mitsubishi Fuso 250 PS after evaluation is 16,504.43 tons / month. The theoretical production of the Mitsubishi Fuso 250 PS after improving work efficiency and ideal road geometry is 20,713.76 tons / month.Keywords : Road Geometry, Production, Work Efficency, Dump Truck, Cycletime.